2018
DOI: 10.1108/jd-04-2017-0057
|View full text |Cite
|
Sign up to set email alerts
|

The preferences of Chinese LIS journal articles in citing works outside the discipline

Abstract: Purpose The purpose of this paper is to understand how Chinese library and information science (LIS) journal articles cite works from outside the discipline (WOD) to identify the impact of knowledge import from outside the discipline on LIS development. Design/methodology/approach This paper explores the Chinese LIS’ preferences in citing WOD by employing bibliometrics and machine learning techniques. Findings Chinese LIS citations to WOD account for 29.69 percent of all citations, and they rise over time.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Åström (2010) studied the relationship between information science and library science as LIS subfields, and found that the different citation patterns in the two areas were indicators of the interdisciplinary nature of LIS. Another example of this methodology is the work of Chen et al (2018), who concluded from an analysis of references that Chinese LIS authors get almost 30% of their information from sources outside of LIS publications. In a similar vein, Levitt and Thelwall (2009) analysed the origins of the top 0.01% citations in the most cited LIS articles in WoS, and observed the importance of links to other disciplines as a factor to explain the greater impact of those works.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Åström (2010) studied the relationship between information science and library science as LIS subfields, and found that the different citation patterns in the two areas were indicators of the interdisciplinary nature of LIS. Another example of this methodology is the work of Chen et al (2018), who concluded from an analysis of references that Chinese LIS authors get almost 30% of their information from sources outside of LIS publications. In a similar vein, Levitt and Thelwall (2009) analysed the origins of the top 0.01% citations in the most cited LIS articles in WoS, and observed the importance of links to other disciplines as a factor to explain the greater impact of those works.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interdisciplinary knowledge transfer involving the import and export of knowledge is an important aspect of knowledge creation (Linderman and Chandrasekaran, 2010) and technology development (Mei and Liu, 2013), as it enhances the impact of research on policy and practice (Fazey et al, 2014). In scientific communities, knowledge import shows the influence of knowledge from outside disciplines (Chen et al, 2018), while knowledge export is an indicator of the scientific strength and impact needed to cross the traditional boundaries of the home discipline (Wormell, 1998). The effective adoption and diffusion of knowledge are the keys to maintaining the value of research achievements and bringing that knowledge into full play (Zhai et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Since 1973, researchers have been trying to update, refine and re-create the discipline-to-dimension relationship (Simpson, 2017; Stoecker, 1993; Xu, 2008) that has enabled the Biglan model to track contemporary discipline development. Dimension I and dimension II have been widely applied to explore disciplinary differences by researchers from a variety of disciplines, such as LIS, education and language and linguistics (Chen et al , 2018, 2020; Durrant, 2017; Huang et al , 2018; Madden et al , 2018; Munk and Thomsen, 2018; Li, 2019). Although the two dichotomies of dimension I and dimension II are challenged by a heterogeneous pattern across disciplines (Prinsloo, 2018), they are currently validated, ever-developing and widely applied in a discipline classification dividing disciplines into four categories: hard-pure, soft-pure, hard-applied and soft-applied.…”
Section: Methodsmentioning
confidence: 99%